USING STORYTELLING TO INCREASE VOCABULARY MASTERY OF ELEMENTARY STUDENTS - M. Asrul Hasby (Journal of English Education and Literature, 2026)
Among the essential components of language learning, vocabulary mastery serves as the foundation for developing listening, speaking, reading, and writing skills. Students with insufficient vocabulary knowledge often experience difficulties in expressing ideas and understanding language input. Traditional vocabulary instruction frequently emphasizes memorization and repetition, which may reduce learners' motivation and engagement. This study aims to investigates the effectiveness of storytelling as a pedagogical strategy to improve vocabulary mastery among elementary school students learning English as a foreign language. Vocabulary acquisition remains a significant challenge for young learners due to limited exposure and traditional teaching approaches. Storytelling offers contextualized, meaningful, and engaging language experiences that can facilitate vocabulary development. This classroom action research involved 30 fifth-grade elementary students of SDN 1 Ampenan in academic year 2025/2026  and was conducted in two cycles. Data were collected through vocabulary tests, observations, interviews, and field notes. The findings revealed a substantial improvement in students' vocabulary achievement, classroom participation, motivation, and confidence. The average score increased from 58.4 in the pre-test to 71.2 after Cycle I and 84.6 after Cycle II. The study concludes that storytelling is an effective instructional strategy for improving vocabulary mastery among elementary students.